THEORETICAL FRAMEWORK FOR CORPORATE REPUTATION MANAGEMENT WITHIN THE CONTEXT OF THE MODERN PARADIGM OF MANAGEMENT - Derevyanko, Olena (Стратегія економічного розвитку України, 2018)
The paper substantiates the main provisions of the theory of corporate reputation in the context of modern management. Therefore, in the 21st century, the place (function) of business in the system of forming a person’s worldview is changing: business in the information economy from a passive recipient of a value system created by religion, family, and culture becomes one of the forces that shape the worldview of its stakeholders. Thus, a new business function is being updated — the formation of a society’s value system in the context of managing the reputation of companies. Modern management of the company’s reputation is developing in line with the concept of «economy of trust»; the essence of the company’s reputation is stakeholder trust. Trust — the socio-psychological basis of reputation, which is the primary cause of the economic interaction of potential investors and businesses, banks and their investors, producers, and consumers, receive cost measurements and is now becoming a full-fledged economic category.